1993
DOI: 10.1086/646675
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcal Ventricular-Peritoneal Shunt Infection: Clinical and Epidemiological Evaluation of Two Closely Associated Cases

Abstract: Our data and previous reports suggest that cryptococcal VP shunt infections appear to be a complication of shunts placed in previously infected persons rather than nosocomial transmission of cryptococcus during placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Clinical studies have reported that patients with cryptococcosis may have developed their disease after a latent infection period of a few months to a few years (20). The finding of cryptococcal infection in two patients after ventriculoperitoneal shunting suggested reactivation of a pre-existing infection (21). These cases suggest the possibility of reactivation, as has been reported for tuberculosis.…”
Section: Discussionmentioning
confidence: 63%
“…Clinical studies have reported that patients with cryptococcosis may have developed their disease after a latent infection period of a few months to a few years (20). The finding of cryptococcal infection in two patients after ventriculoperitoneal shunting suggested reactivation of a pre-existing infection (21). These cases suggest the possibility of reactivation, as has been reported for tuberculosis.…”
Section: Discussionmentioning
confidence: 63%
“…It was observed that the combination drug treatment is capable of disrupting the biofilm with killing the cells as well as disintegrate the biofilm. Biofilm formation has an important role for the C.neoformans to survive within the macrophages and to colonize in the central nervous system (CNS) [ 15 ]. Thus, disrupting the biofilm help to reducing the virulence nature to control the pathogen at the site of infection [ 16 - 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Cryptococcal infection is a rare etiology of VPS infection. Our review of the literature showed that there have been a total of 9 reported cases [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria such as coagulase-negative staphylococci are the most commonly implicated organism [ 4 – 7 ]. Cryptococcus neoformans as a pathogen of VPS infections is rare and the diagnosis using CSF from the shunt can be particularly difficult [ 8 – 10 ]. In immunocompetent patients, cryptococcal antigen tests may be negative, which makes the diagnosis more challenging [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%